Lecturers’ Compliance with Quality Assurance Mechanisms in Public Universities in Delta State - Chinyere, Amini-Philips; E., Omodibo Eguono (European Scientific Journal, ESJ, 2019)
The study investigated the extent to which lecturers’ complied with quality assurance mechanisms in public universities in Delta State. Two objectives, two research questions and two hypotheses guided the study. The descriptive survey research design was adopted. The population of the study consisted of 1,299 lecturers and 6,826 students from the public universities in Delta State. A sample of 260 lecturers and 409 students representing 20% and 6% respectively, of the population was obtained using the proportionate random sampling technique. The instrument used for data collection was a researchers’ made questionnaire titled “Compliance with Quality Assurance Mechanisms Questionnaire (CQAMQ). The Cronbach Alpha method was used to determine the internal consistency of the items and it yielded a result of 0.76 and 0.97 for A and B respectively. The researchers and two assistants distributed 669 copies of the questionnaire and successfully collected 628 copies of the questionnaire administered. The research questions were analyzed using the mean, standard deviation and rank order statistics, while the hypotheses were tested using z-test at 0.05 level of significance. It was found that lecturers in public universities in Delta State complied with measurement and evaluation of students learning outcome and the use of interactive teaching and learning method in the classroom to a high extent. The findings revealed that lecturers’ compliance with measurement and evaluation of students learning outcomes in public universities in Delta State is high. Based on the findings, it was concluded that lecturers complied with the quality assurance mechanisms to a high extent, it was therefore recommended that the university management should formulate a policy that will make lecturers sustain the strategy of assessing the learning outcome ofstudents and organize more lectures and seminars on how lecturers can sustain the strategies in the use of interactive teaching and learning methods in the classroom.